Creating the European Area of Higher Education Voices from the Periphery - Tomusk, Voldemar; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Since 1999 European higher education has been engaged in the most radical reform seen during its 900 years of history. Out of the widely diverse national higher education systems and sub-systems a common European Higher Education Area is being created. This process, driven by the great ideas of establishing federal Europe, is full of tensions and conflicts often ignored in the official discourse. Expanding the project well beyond the borders of the European Union created the difficulty that relatively prosperous and high quality universities in the Western part find themselves side-by-side with much poorer universities of sometimes questionable quality in other parts of the continent. This has led to the rise of many controversial issues, as some of the sponsors of the Process, particularly the European Commission, see international competitiveness of European universities as its most significant goal. The Process is being perceived as following the logic of re-design of European knowledge products for the purposes of the world markets and certain elements of the production process. University communities - academic staff and students - however, sometimes feel that such an approach may not only carry the threat of compromising their vital interests but also call for the revision of the principles of academic autonomy as understood in Europe since the early 19th century. This volume brings together a group of higher education researchers across Europe and looks into the implementation of the Bologna Process in the countries often attributed a peripheral status. Although it is also obvious that if the Process has a center, it stands external to higher education systems and universities it concerns. One can possibly find it either in Brussels or across the Atlantic in the United States, internationally perceived as the main competitor to European higher education. In addition to cultural and political issues the European higher education project faces in various countries, the volume pays particular attention to the role of students as well as the changing position of the intellectuals under its impact. 'This is an important book on a central topic at an important time. It is learned in the best sense, eminently readable and that across many different levels. It is also caustic, deeply ironic and passionate and because passionate, unswervingly provocative.' Professor Guy Neave, Professor of Comparative Higher Education Policy Studies at CHEPS, Universiteit Twente, Netherlands and Director of Research at the International Association of Universities, Paris, France.
Acknowledgments -- Introduction: COM(91) 349 final and the Peripheries of European Higher Education. What is the Point of Bologna in National Reform? The Case of Norwegian Quality Reform in Higher Education. The Bologna Process in Finland: Perspectives from Basic Units -- Searching for the Sub-Plot Between the Lines of Bologna: Qualms and Conservatism of the French Academia in the Face of European Competition. Emergent European Educational Policies Under Scrutiny: The Bologna Process from a Central European Perspective -- The Bologna Process: An Estonian Perspective. What the Bologna Process says about Teaching and Learning Development in Practice: Some Experience from Macedonia. Restructuring Bulgarian Higher Education: The Bulgarian Strategy Towards The Bologna Declaration -- Turkish Academics in Europe: Nomads Chasing a European Dream -- The Challenge of Bologna: The Nuts and Bolts of Higher Education Reform in Georgia. Pizza Bolognese à la Russe: Promise and Peril of the Bologna Process in Russia. European Students in the Periphery of the Bologna Process. The End of Europe and the Last Intellectual: Fine-Tuning of Knowledge Work in the Panopticon of Bologna.
Keywords: EDUCATION; EDUCATION, HIGHER; POLITICAL SCIENCE; EDUCATION; HIGHER EDUCATION; EDUCATIONAL POLICY AND POLITICS; SOCIOLOGY OF EDUCATION; INTERNATIONAL AND COMPARATIVE EDUCATION; POLITICAL SCIENCE